The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12913-017-2287-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care in family planning services in Senegal and their outcomes

Abstract: BackgroundHigh quality of care in family planning (FP) services has been found to be associated with increased and continued use of contraceptive methods. The interpersonal skills and technical competence of the provider is one of the main components of quality of care. To study the process component of quality of care, the distribution of the FP counseling topics was examined by client, provider and facility characteristics. To assess the outcomes of quality of care, client satisfaction and their knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 24 publications
3
38
4
1
Order By: Relevance
“…We found that women who were users of traditional methods were significantly more likely to be switchers to modern methods; traditional method use may be a gateway to more effective method use and therefore these women should be supported in this process. A recent analysis of data collected at health facilities in Senegal found that the general level of counseling for FP was inadequate: only 18% of providers counseled their clients on three items examined by the survey (how to correctly use the method, possible side effects, and when to make a return visit) [ 18 ]. Yet earlier research in Senegal found that women who received good quality care at the time of method initiation were 1.3 times more likely to be using a method after 16 months than were women who did not receive higher quality counseling [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that women who were users of traditional methods were significantly more likely to be switchers to modern methods; traditional method use may be a gateway to more effective method use and therefore these women should be supported in this process. A recent analysis of data collected at health facilities in Senegal found that the general level of counseling for FP was inadequate: only 18% of providers counseled their clients on three items examined by the survey (how to correctly use the method, possible side effects, and when to make a return visit) [ 18 ]. Yet earlier research in Senegal found that women who received good quality care at the time of method initiation were 1.3 times more likely to be using a method after 16 months than were women who did not receive higher quality counseling [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little research exists on effective coverage of family planning and sick-child care. While past research has documented poor quality of clinical care from sources such as SPA surveys, 35–37 to our knowledge, this study is the first to calculate effective coverage of these services using observed measures of clinical quality. Other effective coverage studies have used input measures such as facility type or readiness based on infrastructure and supplies.…”
Section: Discussionmentioning
confidence: 99%
“…Health providers have a role to play in dispelling myths about FP, as well as in helping women find a better-suited method if side effects occur (including nausea, headaches, and menstrual irregularity associated with hormonal methods)44. However, two Service Provision Assessment analyses have found that the quality of FP counselling in Senegal is generally poor, with few providers counselling on side effects and follow-up services in particular4546.…”
Section: Discussionmentioning
confidence: 99%